Assessment and Development of Practical Skills, Creativity of Students (In the example of Pisa) - Aziza Amonova Saydulloyevna; Qobulova Nodira Bahodirovna (Zien Journals, 2022)
This article provides information on assessing and developing students ’creativity based on the PISA program. Noted on evaluation and improvement of PISA tests
Keywords: PISA; IHTT; consultative; creative thinking